Biological Therapies of Severe Asthma and Their Possible Effects on Airway Remodeling - Kardas, Grzegorz; Kuna, Piotr; Panek, Michał (Frontiers in Immunology, 2020)
Asthma is a chronic and heterogenic respiratory tract disorder with a high global prevalence. The underlying chronic inflammatory process and airway remodeling (AR) contribute to the symptomatology of the disease. The most severely ill asthma patients may now be treated using a variety of monoclonal antibodies aiming key inflammatory cytokines involved in asthma pathogenesis. Although clinical data shows much beneficial effects of biological therapies in terms of reduction of exacerbation rates, improvement of lung functions, asthma control and patients’ quality of life, little is known on the effects of these monoclonal antibodies on AR – a key clinical trait of long-term asthma management. In this review, the authors summarize the data on the proven effects of monoclonal antibodies in asthma on AR. To date, in terms of reversing AR, the mostly studied was omalizumab. However, some studies also addressed this clinical issue in context of other severe asthma biological therapies (mepolizumab, benralizumab, tralokinumab). Still, data on effects of particular biological therapies on AR in severe asthma are incomplete and require further studies. According to the American Thoracic Society research recommendations, future research shall focus on AR in asthma and improve drugs targeting AR, including the available and future monoclonal antibodies.